2018
DOI: 10.12659/ajcr.907178
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Modulation of Portal Venous Pressure by Splenectomy Saves the Patient with Liver Failure and Portal Hypertension After Major Hepatectomy: Is Delayed Splenectomy an Acceptable Therapeutic Option for Secondary Portal Hypertension?

Abstract: Patient: Female, 56Final Diagnosis: Secondary portal hypertensionSymptoms: Intractable ascitesMedication: —Clinical Procedure: SplenectomySpecialty: Gastroenterology and HepatologyObjective:Unusual clinical courseBackground:Major or aggressively-extended hepatectomy (MAEH) may cause secondary portal hypertension (PH), and postoperative liver failure (POLF) and is often fatal. Challenges to prevent secondary PH and subsequent POLF, such as shunt creation and splenic arterial ligation, have been reported. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Major or aggressively extended hepatectomy for liver cancer may give rise to secondary portal hypertension (PH), which would arouse massive ascites, edema, and refractory hemorrhage [38]. Kamanaka et al [36] found significantly lower blood flow of portal vein and congestion index in cirrhotic patients undergoing splenectomy, which was associated with lower ET-1 and increased NO and contributed to amelioration of complications related to secondary PH such as ascites and upper gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Major or aggressively extended hepatectomy for liver cancer may give rise to secondary portal hypertension (PH), which would arouse massive ascites, edema, and refractory hemorrhage [38]. Kamanaka et al [36] found significantly lower blood flow of portal vein and congestion index in cirrhotic patients undergoing splenectomy, which was associated with lower ET-1 and increased NO and contributed to amelioration of complications related to secondary PH such as ascites and upper gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported to improve function (increase in prothrombin time, platelet and albumin levels) in patients with HCC and concomitant hypersplenism (102). However, the role of splenectomy post-hepatectomy is unclear, but may have a therapeutic potential to treat PHLF (103). Splenic artery ligation (SAL) is an alternative to splenectomy intraoperatively to reduce PVP in PHLF or SFSS.…”
Section: Splenectomymentioning
confidence: 99%
“…The rebleeding rate was 13.04%, much higher than that reported in previous studies. The complication PVT should not be the main cause of rebleeding because only one of six patients who rebled had PVT and a much longer follow-up time (12-129 months vs 4-75 months), hepatectomy might cause secondary portal hypertension 35 , and tumor in ltration might aggravate portal hypertension 36 .…”
Section: Discussionmentioning
confidence: 99%